Figurka zoomorficzna ze stanowiska Beszyn 7, powiat włocławski - Piotrowska, Magdalena; Kot, Karolina (Acta Universitatis Lodziensis. Folia Archaeologica, 2011)
One of the most interesting artifacts obtained from a multicultural site at Beszyn was a small zoomorphic figurine. It is highly probable, that this artifact could be connected with the Lusatian culture. The figurine, despite being in a good state of preservation, has few anatomical details, which would allow for the identification of the species of animal. It seems that the artifact under consideration is a schematic representation of a cow or a bull, but may not have been connected with the sphere of beliefs of its producers. To determine the material of which the artifact was made it was subjected to specialized metallographic analyzes. The obtained results turned out to be very interesting. In the available metallographic database, as well as in the literature it was unsucessful to nd an object of similar chemical composition. The analyzes showed that the artifact was made of tin and lead bronze. The copper alloy used seems to be unprecedented because of its iron, silver, and manganese contents, which occur in the case of iron alloys, not copper ones. These are supplements that raised corrosion resistance of the alloy. It should be emphasized that in modern and medieval alloys no analogical chemical composition was found, which together with the forms of corrosion sediments indicates its early origin – a long period of the artifact’s deposition in soil.